Mitogenomic features of the citrus leafminer, Phyllocnistis citrella (Lepidoptera: Gracillariidae) and the related mitogenomic phylogeny. Issue 3 (2nd July 2020) - Liu, Hong-Ling; Chen, Zhi-Teng; Chen, Song; Chen, Qing-Dong; Pu, De-Qiang; Liu, Yue-Yue; Liu, Xu
Abstract: The complete mitochondrial genome of the citrus leafminer, Phyllocnistis citrella (Lepidoptera: Gracillariidae) was sequenced for the first time, which was 15, 416 bp in length and with an A + T content of 81.9%. The common set of 37 genes (13 PCGs, 22 tRNA genes, and two rRNA genes) were all annotated. Most PCGs had standard ATN start codons and TAN stop codons. Most tRNA genes exhibited typical cloverleaf secondary structures, whereas the dihydrouridine (DHU) arm of trnSer (AGN) was reduced. The mitochondrial phylogenetic analyses consistently recovered the relationships within Gracillariidae.